Revising Wolff's support for retribution in theories of punishment: desistance, rehabilitation, and accommodating individual and social accounts of responsibility. Issue 4 (1st October 2016) - Deering, John; Smith, Steven R.
ABSTRACT: Jonathan Wolff supports retribution as a justification for punishment in his book Ethics and Public Policy: A Philosophical Enquiry, arguing that the victim's status and self-respect has been undermined by a crime committed. Punishment responds to these 'social violations', with the criminal justice system acting as a 'communicative mechanism' to the offender and victim, restoring the status of the victim by punishing the offender. Consistent with Wolff's 'bottom-up' methodological approach to applied ethics, this paper defends his conclusions supporting retribution, for certain crimes at least, but his position needs qualifying and supplementing. We mount a defence of retribution which, contrary to popular views, seeks to accommodate both individual and social accounts of responsibility. This accommodation is achieved by holding the individual offender responsible via retributive justifications of punishment, while also acknowledging the social responsibility of restoring the status of the offender given the social injustice experienced by many offenders, prior to their offending. Following this analysis, and a consideration of empirical studies concerning probation practice, we recommend the practice of desistance as most likely to help reduce re-offending, alongside the social responsibility of other state representatives and social institutions for building socio-economic capital for the offender.